A Modified Buffered Adaptive Algorithm for Routing in Optical Benes Network - Kaur, Tanvir (My University, 2011)
One of the main issues with optical networks is the problem of blocking that affects the performance of the network. Several approaches have been established in order to turn a blocking network into a non-blocking one. These approaches can be classified as strictly non-blocking, wide sense non-blocking and rearrangeably non-blocking. Out of all these approaches the rearrangeably non-blocking networks has been discussed in this thesis. Benes network is a long established rearrangeable network to connect large switching elements. This network has the characteristic of providing multiple paths for same output request. For providing different paths several routing algorithms have been proposed in the literature.While designing the routing algorithms, attention must be paid towards the performance of the network in delivering the data packets to the required destination without blocking the network in between the different stages of the network. However in the existing partially adaptive routing algorithm, discussed in this thesis, blocking of the network was taking place whenever multiple data packets tried to use the network simultaneously. In this thesis, a new routing algorithm named Modified Buffered Adaptive Routing algorithm has been proposed. The proposed algorithm uses buffers to improve the network performance by removing the conflicts occurring with the existing partially adaptive routing algorithm and by handling multiple inputs at a time. The results have been shown on how the proposed algorithm improves the performance in terms of removal of routing conflicts.
M.E. (Software Engineering)
Keywords: blocking network